How do taxes affect investment when firms face financial constraints? - Martin Simmler (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This study uses a switching regression framework with known sample separation to analyze the effects of corporate income taxation on investment in case of binding and non-binding financial constraints. By employing two different sample splitting criteria, payout behavior and the ratio of liabilities to total assets, I show that the elasticity of capital to its user costs in an auto-distributed-lag model is underestimated in case of neglecting the presence of financial constraints. For unconstrained firms, the elasticity of capital to its user costs is around -1. For financially constrained firms the elasticity is statistically not different from zero. For the latter group instead, the results prevail by using the effective average tax rate to measure liquidity outflow through taxation that corporate taxation affects investment through changing internal finance. In addition, this study helps to understand the methodological differences between auto-distributed-lag and error-correction models.
Keywords: H25; H32; G31; 330; Investment cash flow sensitivity; financial constraints; taxation; effective average tax rate; effective marginal tax rate; switching regression